2013
DOI: 10.1111/jai.12318
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of differential protein expression in the skin of zebrafish [Danio rerio (Hamilton, 1822)] infected with Aeromonas hydrophila

Abstract: Summary Skin is an important component of the mucosal immune system in fish, however its molecular mechanism at the proteome‐level remains unclear. In this study, differentially expressed proteins in the skin of zebrafish Danio rerio responding to Aeromonas hydrophila infection were identified using two‐dimensional gel electrophoresis (2‐DE) coupled with mass spectrometry (MS) analysis. The results showed that 17 proteins were differentially expressed, six proteins of which were up‐regulated and 11 proteins do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several high-throughput protein assays have been conducted in various fish to determine the molecular mechanism of fish skin as a pathogen barrier at the proteome-level. A previous study identified 17 proteins differentially expressed in zebrafish ( Danio rerio ) skin under Aeromonas hydrophila infection, and these included the DR α 1 domain of the MHC class II and the immunoglobulin heavy chain V-region ( 21 ). Another study on the differential proteomics of the zebrafish skin in response to SVCV infection examined the by isobaric tags for relative and absolute quantitation (iTRAQ).…”
Section: Discussionmentioning
confidence: 99%
“…Several high-throughput protein assays have been conducted in various fish to determine the molecular mechanism of fish skin as a pathogen barrier at the proteome-level. A previous study identified 17 proteins differentially expressed in zebrafish ( Danio rerio ) skin under Aeromonas hydrophila infection, and these included the DR α 1 domain of the MHC class II and the immunoglobulin heavy chain V-region ( 21 ). Another study on the differential proteomics of the zebrafish skin in response to SVCV infection examined the by isobaric tags for relative and absolute quantitation (iTRAQ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the miRNAs interacting with the target genes and proteins were not only associated with immune response ( 7 , 45 ) but also played important roles in regulating the regulators of the immune network ( 28 , 58 ). In M. miiuy infected with Vibrio harveyi , miR-148 targeted and negatively regulated the expression of the MyD88 gene, and overexpression of miR-148 inhibited the inflammatory cytokine production of both IL-6 and IL-1β ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation was similar to other fish-virus and bacterial studies [ 123 , 124 ], highlighting it as a therapeutic target for virus or bacteria-associated diseases. Furthermore, the proteomics approach of zebrafish skin infected with Aeromonas hydrophila revealed the increased expression of actin, myosin heavy chain, and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) [ 125 ]. The expression of both actin and myosin in the skin indicated that these proteins are important for the skin response of zebrafish to A. hydrophila infection.…”
Section: Multi-omics Perspective On Infectious Fish Diseases Studiesmentioning
confidence: 99%
“…It was suggested that the increased disease resistance in fish might be associated with the low expression of myosin. A low expression of myosin was proposed to inhibit muscle growth, which inhibits further pathogen infection [ 125 ]. Meanwhile, GAPDH was reported to have multiple roles in immune function, defense responses, antioxidant, and energy metabolism in fish [ 131 ].…”
Section: Multi-omics Perspective On Infectious Fish Diseases Studiesmentioning
confidence: 99%